Salvia officinalis in dentistry - Nikhita Narayanan; Lakshmi Thangavelu (Wolters Kluwer Medknow Publications, 2015)
Salvia officinalis is a medicinal herb used as an cosmetic, flavoring agent, It has antibacterial, antifungal, anticaries, antiplaque, antiviral, astringent, and other useful properties, it is also used in dental practice for the management of periodontal disease and to prevent halitosis. The objective of this article is to highlight various uses of S. officinalis in the dental field along with its use in medical problems.